Effect of potassium addition and several levels of nitrogen on growth and yield of two cultivars of wheat under sprinkler irrigation system - Hasaen, Saleam Abbas; AL-Hade, Muhammed Qassim Safi; Ameer, Ahmed Neamah Abdul; Jawad, Nawres Neamah (Journal of Kerbala for Agricultural Sciences, 2019)
For the purpose of evaluating the effect of adding the potassium and several levels of nitrogen in the growth and yield two cultivars of wheat under sprinkler irrigation system. Afield experiment was carried out during the 2016-2017 season in Ain Tamur in Karbala City. The study contained two factors. The first factor was two cultivars of wheat Adnan 99 and G5 while the second factor was addition of chemical fertilizers T1 addition of 200 kg h-1 of urea without adding potassium, T2 addition of 260 kg h-1 of urea without adding potassium, T3 addition of 400 kg h-1of urea without adding Potassium, T4 addition of 200 kg h-1 of urea and 50 kgh-1of potassium sulphate, T5 addition of 260 kg h-1of urea and 50 kgh-1 of Potassium Sulphate, T6 addition of 400 kgh-1of urea and 50 kgh-1 of potassium. The Randomized Complete Block Design (RCBD) was used with two factors and five replicates. The results showed the exceeding of Adnan 99 cultivar by giving the highest rates of spike length 7.34 cm, grains number in the spike 32.30 grain spike-1, weight of 1000 grains 35.16 gm, grains yield 2.58 ton h-1 harvest index 34.9%; and the exceeding of G5 in the plant height 60.88 cm, spikes number 283.6 spike m-2, and biological yield 7.71 ton h-1. In addition, the results showed the exceeding of T6 treatment by giving the highest rates of plant height 67. 29 cm, spikes number 320.5 spike m-1, spike length 8.77 cm, weight of 1000 grain 37.75 gm grains yield 3.57 ton h-1, biological yield 10.00 ton h-1 , and harvest index 36.3%.The results also showed a significant interaction between Chemical fertilization and cultivars in the most studied characters. It can be concluded from this study that the addition of potassium and nitrogen has anobvious effect in increasing grain yield.